Na drodze do publicznej służby zdrowia. Meandry polityki zdrowotnej drugiej rzeczypospolitej - Grata, Paweł (Polityka i Społeczeństwo, 2020)
In the Second Republic of Poland health protection was insufficiently developed. There were very few doctors, nurses and hospitals. Only people who were insured or the wealthy had access to medical treatment. The majority of citizens, especially rural residents, could not use health care. The health policy of the state was passive for many years. Changes appeared only in the mid-thirties. The aim of health policy was a public health service for all citizens. The authorities declared their support for this idea on a number of occasions and the parliament accepted the law of public health in June 1939. It was the basis for the construction of common access to healthcare in Poland. To achieve this aim, health centres were built and the compulsory medical practice for the doctors was introduced in villages. The beginning of the Second World War prevented the enforcement of this Act. However, the attempt to create a public health service made in the Second Republic of Poland was a proof of progress which has been made in state health policy.